ASSOCIATIONAL TYPES OF PERI-FAULT METASOMATITES AND THEIR GEOCHEMICAL PROPERTIES - Sobachenko V.N. (My University, 1989)
Peri-fault metasomatites of the associational types discussed differ in chemical bias or specialization (Table 1). The subalkalic feldspathic metasomatites containing lepidomelane tend to concentrate Be, Nb, Ta and the lighter lanthanides. The typomorphic elements of the low-temperature metasomatites of type I are radio-active elements and Sr and Ba. The alkalic feldspathic metasomatites show a distinct specialization in that they tend to concentrate Ta, Nb, Zr and Hf and for light and the heavier lanthanides, fluorine and, to a lesser degree, Rb, Li, Sn and Zn. The typomorphic minor elements of peri-fault silicate-carbonate metasomatites and asociated carbonatites are Nb, P, Sr and Ba. The chemical and isotopic data that are presented in support of classification of the peri-fault metasomatites into the principal associational types indicate that the differences in their specialization and ore contents (described above) are largely the result of significant differences in the compositions and sources of the metasomatism-producing fluids, and are only partially caused by the facies conditions under which the metasomatites were generated.